Economic Analysis of Sequestering Carbon in Green Ash Forests in the Lower Mississippi River Valley - Ching-Hsun Huang; Gary D. Kronrad; Shiaolin D. Cheng (The Scientific World Journal)
Since the U.S. is the largest emitter of carbon dioxide (CO2), it has become crucial to develop options that are both cost effective and supportive of sustainable development to reduce atmospheric CO2. Electric utility companies have the options of reducing their use of fossil fuels, switching to alternative energy sources, increasing efficiency, or offsetting carbon emissions. This study determined the cost and profitability of sequestering carbon in green ash plantations, and the number of tons of carbon that can be sequestered. The profitability of green ash is $2,342 and $3,645 per acre on site indices (measurement of soil quality) 65 and 105 land, respectively, calculated with a 2.5% alternative rate of return (ARR). These figures shift to –$248 and –$240 calculated with a 15.0% ARR. If landowners who have an ARR of 2.5% can sell carbon credits for $10 per ton of carbon, profits will increase by $107 per acre on poor sites and $242 on good sites. Over one rotation (cutting cycle), 38.56 net tons of carbon can be sequestered on an acre of poor quality land and 51.35 tons on good quality land. The cost of sequestering carbon, without including revenues from timber production and carbon credits, ranges from a high of $15.20 per ton on poor sites to $14.41 on good sites, calculated with a 2.5% ARR; to a high of $8.51 per ton on poor sites to $7.63 on good sites, calculated with a 15.0% ARR. The cost of storing carbon can be reduced significantly if the trees can be sold for wood products.